GLOBALIZATION OF PEDIATRIC CLINICAL TRIALS AND CONTEXT OF VULNERABILITY: A NECESSARY RISK! - DAHANE, Neyla; GODARD, Béatrice (MEDECINE LEGALE DROIT MEDICAL, 2025)
In a context of change in the distribution of research where the relocation of clinical trials is at work, it seems inevitable that more and more research will be carried out in low and middle income countries. This migration of research must be accompanied by an awareness of the specific and glaring needs of the pediatric population. Indeed, there is a large deficit in research on children, especially for diseases particularly affecting children in low and middle income countries, such as certain infectious diseases. This is explained in particular by the many constraints that exist around pediatric clinical trials. These trials must however be subject to rigorous supervision to avoid drifts and the risk of abuse, while not being too rigid to allow sensitivity to the local context. In this perspective, more reflections must be carried out to reconcile principles which could seem in tension namely, on the one hand, the protection of the extremely vulnerable populations that are children in low-income countries, and on the other hand, the principle of justice in the distribution of clinical trials and the urgent need for research for this population.